Crystal structures and electrical properties of cobalt manganese spinel oxides. (December 2020) - Park, Kyoung Ryeol; Han, HyukSu; Hou, Dong; Jones, Jacob L.; Oh, Nuri; Ahn, Chisung; Lee, Jaewoong; Lee, Seung Hwan; Mhin, Sungwook
Abstract: Crystal structures and hopping motions of cobalt manganese spinel oxides across a wide composition range (Co x Mn3− x O4 (CMO), 0.9 ≤ x ≤ 2.7) are investigated in order to clarify the corresponding mechanisms of electrical behaviors as negative temperature coeﬃcient thermistors. Based on the diffraction measurements, a tetragonal to cubic spinel transition are observed mostly with increasing Co content. Hopping distance for a series of CMO are calculated by the variable range hopping mechanism, which is changed as a function of composition, resulting to the observed unique electrical properties. According to the electrical and structural analysis, the electrical properties of CMO compounds with different Co contents majorly determined by tetragonal to cubic phase transition, cation distribution, and hopping distance. In addition, the formation of secondary phase (i.e., CoO) and another CMO phase may also significantly affect the electrical properties.